2005
DOI: 10.1007/s00299-005-0028-y
|View full text |Cite
|
Sign up to set email alerts
|

Successful development of a shed-microspore culture protocol for doubled haploid production in Indonesian hot pepper (Capsicum annuum L.)

Abstract: Various systems of anther and microspore cultures were studied to establish an efficient doubled haploid production method for Indonesian hot pepper (Capsicum annuum L.). A shed-microspore culture protocol was developed which outperformed all the previously reported methods of haploid production in pepper. The critical factors of the protocol are: selection of flower buds with more than 50% late unicellular microspores, a 1 day 4 degrees C pretreatment of the buds, followed by culture of the anthers in double-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
101
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(118 citation statements)
references
References 30 publications
6
101
3
Order By: Relevance
“…Anther cultures have been used in a number of cultivars with relative efficiency (reviewed in Irikova et al 2011;Seguí-Simarro et al 2011), but successful application of microspore cultures has only been reported in few hot (asian) pepper types (Kim et al 2008;Supena et al 2006b). Nevertheless, the stages most sensitive to inductive treatments in pepper revolve around the VM and YBP (Irikova et al 2011), exactly the same described for most of the known inducible species.…”
Section: Introductionmentioning
confidence: 99%
“…Anther cultures have been used in a number of cultivars with relative efficiency (reviewed in Irikova et al 2011;Seguí-Simarro et al 2011), but successful application of microspore cultures has only been reported in few hot (asian) pepper types (Kim et al 2008;Supena et al 2006b). Nevertheless, the stages most sensitive to inductive treatments in pepper revolve around the VM and YBP (Irikova et al 2011), exactly the same described for most of the known inducible species.…”
Section: Introductionmentioning
confidence: 99%
“…Kott et al (1988) postulated that some toxic compounds could be released from nonembryonic microspores into the medium, which would harm potential embryogenic microspores and reduce the embryogenic frequency. So far, AC has been used with B. campestris (Guo and Pulli, 1996), B. napus (Gland et al, 1988), B. oleracea (da Silva Dias, 1999, and pepper (Supena et al, 2006;Cheng et al, 2013) to improve embryogenesis. In B. campestris, 150 mg/L AC improved embryo quality as well as the quantity of embryos by two-to fivefold.…”
Section: Discussionmentioning
confidence: 99%
“…Using this method, Supena et al (2006) reported that only 0.1 plants regenerated per flower bud. Kim et al (2008) suggested a different protocol for microspore culture leading to a higher frequency of embryo production and plant regeneration (4 plants/flower bud).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative method to obtain DH plants from a male nucleus in vitro is shed-microspore culture, based on anther culture systems with a double-layer medium (Supena et al, 2006). Supena and Custers (2011) achieved the induction of a significantly higher percentage of normal-looking embryos (from 20% to 50%) in Indonesian hot pepper.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation